Post-treatment change in Mycobacterium tuberculosis antigen-stimulated tumor necrosis factor-alpha release in patients with active tuberculosis - Kim, Chang Ho (J Thorac Dis, 2015)
BACKGROUND: Monitoring tuberculosis (TB) treatment response remains challenging due to lack of reliable laboratory markers. In recent years, increased efforts have been exerted toward development of new biomarkers reflecting treatment response appropriately. While performance of interferon-gamma release assays (IGRAs) to monitor anti-TB treatment has been extensively evaluated, there is no data about post-treatment changes in Mycobacterium tuberculosis (MTB) antigen-stimulated tumor necrosis factor-alpha (TNF-α) release in active TB patients. Herein, we explored whether the MTB antigen-stimulated TNF-α release would be useful for monitoring responses to anti-TB treatment. METHODS: We compared unstimulated (TNF-α(Nil)), MTB antigen-stimulated (TNF-α(Ag)), and MTB antigen-stimulated minus unstimulated TNF-α levels (TNF-α(Ag-Nil)) in supernatants from QuantiFERON-TB Gold In-Tube tests before and after treatment in 16 active TB patients, 25 latent TB infection (LTBI) subjects, and 10 healthy controls (HC). RESULTS: TNF-α(Ag) and TNF-α(Ag-Nil) levels decreased significantly after treatment in patients with active TB. In addition, TNF-α(Nil), TNF-α(Ag), and TNF-α(Ag-Nil) levels were significantly higher in untreated active TB patients compared to LTBI subjects and HC. CONCLUSIONS: This finding cautiously suggests that MTB Ag-stimulated TNF-α response may be a potential adjunctive marker for monitoring treatment response in active TB patients.